Biotransformation of diethenylbenzenes. IV. A simple high-performance liquid chromatographic method for separation of urinary metabolites of 1,3-diethenylbenzene on analytical and semi-preparative scales - Linhart, Igor; Vosmanská, Magda; Mitera, Jiří; Šmejkal, Jaroslav (Journal of chromatography, 1992)
A simple ion-suppression separation on reversed-phase columns, which is applicable for both analytical and semi-preparative work, is described. Six urinary metabolites of 1,3-diethenylbenzene (I), namely 1-(3-ethenylphenyl)-1,2-dihydroxyethane beta-D-glucosiduronates (two isomers, II and III), N-acetyl-S-[1-(3-ethenylphenyl)-2-hydroxyethyl]cysteine (IV), N-acetyl-S-[2-(3-ethenylphenyl)-2-hydroxyethyl]cysteine (V), 3-ethenylphenylmandelic acid (VI) and 3-ethenylphenylglyoxylic acid (VII), were isolated (Fig. 1). Four of them, IV-VII, have been identified in our previous work; the two glucosiduronates were identified for the first time by 1H NMR spectroscopy, fast atom bombardment mass spectrometry, and enzymic hydrolysis yielding 1-(3-ethenylphenyl)-1,2-dihydroxyethane as an aglycone. The method was reproducible the concentration range 0.05-5 mg/ml, the coefficient of variation being less than 7% (n = 5). Excretion of II-VI within 24 h in the urine of rats dosed with a single intraperitoneal injection of 100, 300 and 600 mg/kg I was determined quantitatively. The utility of the method is discussed in comparison with gas chromatographic-mass spectrometric techniques used previously.
Keywords: styreny; Biotransformation; Rats, Wistar; vysokoúčinná kapalinová chromatografie; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; potkani Wistar; reprodukovatelnost výsledků; Reproducibility of Results; Chromatography, High Pressure Liquid; krysa rodu Rattus; Spectrophotometry, Ultraviolet; Animals; biotransformace; ženské pohlaví; zvířata; Rats; Styrenes; Female; spektrofotometrie ultrafialová